Belgesel sinemanın bakış açısından sanat ve zanaat malzemesi olarak kurşun “mantıka tokmak” - Maniş, Rıfat (My University, 2012)
Tezimin ana konusu, Romalılar döneminde başlayıp Osmanlılar döneminde yaygınlık kazanan Kurşun kaplama mesleğidir. Tezim genel olarak iki bölümden oluşmaktadır. Birinci bölümde kurşun kaplama mesleğini Vakıflar Genel Müdürlüğü bünyesinde işçi olarak çalıştığı dönemde, Klasik Osmanlı Terbiyesi ile öğrenmiş olan, Rahmi Maniş ve onunla birlikte mesleği icra eden dört oğlunun ustalıklarının anlatıldığı Mantıka Tokmak adlı belgesel filmdir. İkinci bölüm tezin yazılı kısmı olup sanat ve zanaat malzemesi olarak kurşunu ele almaktadır. Belgesel filmde bir öykü kurgusundan daha çok lirik bir şiir kurgusunu kullanmayı hedefledim. Filmin devamlılığını, kurşun kaplama mesleğinin yapım süreçleri üzerinden sağlamaya çalıştım. İzleyiciyi kısa bir zaman diliminde de olsa mesleğin icra edildiği ortamlara taşımayı amaçladım. İkinci bölümünde, yani tezin yazılı kısmında, öncelikle kurşun madeninin kimyasal ve fiziksel özelliklerini, sonrasında kullanım alanlarını, çeşitli kaynaklar ışığında belgelemeye çalıştım. Kurşun madeninin sanat ve zanaat malzemesi olarak kullanıldığı alanlar için özel bölüm açtığım tezimin bu ikinci bölümünde, özellikle kurşun kaplama mesleğinin tüm yapım süreçlerini, mesleğin tüm ayrıntılarını ve püf noktalarını anlatmaya çalıştım

The main subject of my thesis is the craft of “lead coating” which began to be exercised in the Roman period and which became common during the Ottoman period. The thesis consists of two general sections. The first part is made up of the documentary film, “Mantıka Tokmak” (Turkish term for special mallet used in lead coating), recounting the mastery of Rahmi Maniş, who had learned the art of lead coating in the classical Ottoman discipline where he was a worker for “Vakıflar Genel Müdürlüğü” (Department of Foundations), and his four sons, who practice the craft with him. The second part consists of the written texts exploring the uses of lead as a material in the arts and crafts. In the documentary film, I aimed to use the style of lyric-poetic editing, rather than a story line. I attempted to achieve the continuity of the film by way of the different stages of production in the craft of lead coating. I tried if only for a short slice of time, to carry the spectator to the environments where the craft is actually exercised. In the second part, that is, in the written part of the thesis, I tried first to document the chemical and physical aspects of the element of lead, and then the different uses of this element, in the light of various sources. In this second part of the thesis whose I also created a special chapter for the uses of the element of lead as a source material in the arts and crafts, I especially attempted to explain the whole of the various stages of production, all of the details of the craft, and all the special tips and tricks concerning the art of lead coating.
Keywords: Film; Sinema; Zanaat_Kurşun Kaplama